Etymologie ludowe w toponimach na pograniczu polsko-ruskim - Kij, Monika (Słowo. Studia językoznawcze, 2020)
Toponyms are interesting linguistic material. They contain knowledge about the environment of our existence - its formation, wealth, history, and even about spatial or social relations. The purpose of this article was to obtain and analyse naming material (names and their folk etymologies) from seventeen villages located within three rural communes on both sides of the San River. The analysis was based on comparison of folk and scientific etymologies. This allowed to answer the questions of how current residents of the former ethnic borderland understand foreign names in their localities, what kind of conceptualisation of the world emerges from folk etymologies, and whether the river San as a natural obstacle significantly influenced the linguistic concepts of its right and left-bank residents. The analysis of toponyms indicates that in rural communities of the studied area, proper names were often motivated by historical, settlement and topographic specifics. Therefore, simple motivation dominates here: creators most often referred to physical properties such as shape and appearance. From other aspects, location, function and local residents were often considered. The relatively high percentage of names with foreign phonetic influences, largely incomprehensible to their contemporary users, stems from the turbulent history of this area and the overlapping Ruthenic, Slovak and other influences. No statistically important differences in conceptualisation of the world between the residents of the east and west sides of the river were detected.